Effects of Zr/Ti ratio and sintering temperature on Structural and electrical properties of PFN-PNN-PZTceramics near the morphotropic phase boundary - Ben Amor, Loubna; Boutarfaia, Ahmed; Bentouila, Omar (Journal of Applied Engineering Science & Technology; Vol 4 No 1 (2018), 2018)
0.05Pb[Fe 1/2 Nb 1/2 ]O 3 -0.05Pb[Ni 1/ 3 Nb 2/3 ]O 3 -0.90Pb[Zr x Ti (1-x) ]O 3 [PFN-PNN-PZT] quaternary piezoelectric ceramics with varying Zr/Ti ratios located near the morphotropic phase boundary (MPB) were prepared by a conventional mixed-oxide route. The samples structure was determined by X-ray diffractometry which indicate that the phase structure, of sintered PFN-PNN-PZT ceramics, was transformed from tetragonal to rhombohedral with Zr/Ti ratio increased in system. The effect of Zr/Ti ratio and sintering temperature on the structure and piezoelectric properties of our simples were investigated. The new MPB in this quaternary system with optimum piezoelectric properties was found at x = 0.51-0.53. The dependence of the piezoelectric coefficient (d 31 ), electromechanical coupling factor ( kp ) and the dielectric constant ( ε ) on the Zr/Ti ratio shows a pronounced  maximum of d 31 = 141* 10 -12 C/N, kp = 0.64 and ε = 850 at Zr/Ti : 51/49. As the Zr/Ti ratio increases, the Tc of PFN-PNN-PZT ceramics decreases and consequently the peak in the dielectric spectrum corresponding to the Tc moves towards room temperature. A Tc of 360 °C is obtained when Zr/Ti: 51/49.